Predictors of Pain Recurrence After Lumbar Facet Joint Injections - Campos, Wuilker Knoner; Linhares, Marcelo Neves; Sarda, Jamir; Santos, Adair Roberto Soares; Lin, Kátia; Latini, Alexandra; Walz, Roger (Frontiers in Neuroscience, 2019)
Introduction: Facet joint injections (FJI) of anesthetic and corticosteroids is useful for the diagnosis and treatment of low back pain (LBP). Here we evaluated the efficacy of FJI on LBP treatment and the predictive variables of pain recurrence after FJI. Methods: We followed prospectively forty-three consecutive patients with chronic LBP treated with FJI. Clinical assessments were carried out at baseline one week before FJIs and after a 6-month follow-up visit using the visual analog scale (VAS) for pain, Oswestry Disability Index (ODI) for disability-specific measure and MacNab criteria for global effectiveness and compared by analyzed by paired-samples “t” tests. Multiple cox-regression analysis was used to identify the presurgical variables independently associated with pain recurrence anytime during the follow-up. In addition to the demographic, clinical, and surgical data, we also analyzed psychometric scales: Pain Catastrophizing Scale (PCS), Beck Anxiety Inventory (BAI), and Beck Depression Inventory (BDI). Results: After 6-month follow-up, thirty-two patients (74.4%) showed a clinically significant reduction of pain and twenty-seven (62.8%) reported a clinically significant improvement of disability. Presurgical catastrophizing (PCS score ≥ 5, adjusted HR 4.4, CI 95% 1.7–11.3, p=0.002) and smoking (Adjusted HR 12.5, CI 95% 1.1 – 138.9, p = 0.04) remains associated with pain recurrence. Conclusions: FJI reduces low back pain and disability of patients with unresponsive LBP. Pain-related cognitive and behavioral factors determined by pain catastrophizing and smoking were independently associated with pain recurrence after lumbar FJI. The results support the need for a multidisciplinary approach for presurgical evaluation of patients with chronic pain.